Risky sexual behavior and associated factors among reproductive age women in eastern African countries: a multilevel analysis of the recent demographic and health survey - Belayneh Shetie Workneh; Alebachew Ferede Zegeye; Tadesse Tarik Tamir; Enyew Getaneh Mekonen (BMC, 2024)
Abstract Introduction Risky sexual behavior exposes an individual to the risk of contracting sexually transmitted infections including human immunodeficiency virus (HIV). Even though risky sexual behavior is a devastating problem in low- and middle-income countries, studies on risky sexual behavior and associated factors among reproductive-age women in Eastern African countries are limited. Therefore, this study aimed to assess the magnitude of risky sexual behavior and associated factors among reproductive-age women in Eastern African countries that help to target high-risk groups and set appropriate intervention. Method The appended and recent Demographic and Health Survey dataset of 10 Eastern African countries from 2012 to 2022 was used for data analysis. A total of 111,895 participants were included in this study as a weighted sample. Associated factors were determined using a multilevel mixed-effects logistic regression model. Significant factors in the multilevel mixed-effect logistic regression model were declared significant at p-values < 0.05. The adjusted odds ratio (AOR) and confidence interval (CI) were used to interpret the results. Result The overall magnitude of risky sexual behavior among reproductive-age women in Eastern African countries was 28.16% (95% CI 27.90%, 28.43%), which ranged from 3.80% in Ethiopia to 67.13% in Kenya. In the multivariable analysis, being a younger woman, being an educated woman, being tested for human immunodeficiency virus, having work, drinking alcohol, and being an urban dweller were factors that were significantly associated with higher odds of risky sexual behavior. Conclusion The overall magnitude of risky sexual behavior among reproductive-age women in Eastern African countries was high. Individual-level (being a younger woman, being an educated woman, being tested for human immunodeficiency virus, having work, and drinking alcohol) and community-level (being an urban dweller) variables were associated with higher odds of risky sexual behavior. Therefore, policymakers and other stakeholders should give special consideration to urban dwellers, educated, worker and younger women. Better to improve the healthy behavior of women by minimizing alcohol consumption and strengthening HIV testing and counseling services to reduce the magnitude of risky sexual behavior.